Hit and Run Transcriptional Repressors Are Difficult to Catch in the Act. (27th June 2019) - Shah, Manan; Funnell, Alister P. W.; Quinlan, Kate G. R.; Crossley, Merlin
Abstract : Transcriptional silencing may not necessarily depend on the continuous residence of a sequence‐specific repressor at a control element and may act via a "hit and run" mechanism. Due to limitations in assays that detect transcription factor (TF) binding, such as chromatin immunoprecipitation followed by high‐throughput sequencing (ChIP‐seq), this phenomenon may be challenging to detect and therefore its prevalence may be underappreciated. To explore this possibility, erythroid gene promoters that are regulated directly by GATA1 in an inducible system are analyzed. It is found that many regulated genes are bound immediately after induction of GATA1 but the residency of GATA1 decreases over time, particularly at repressed genes. Furthermore, it is shown that the repressive mark H3K27me3 is seldom associated with bound repressors, whereas, in contrast, the active (H3K4me3) histone mark is overwhelmingly associated with TF binding. It is hypothesized that during cellular differentiation and development, certain genes are silenced by repressive TFs that subsequently vacate the region. Catching such repressor TFs in the act of silencing via assays such as ChIP‐seq is thus a temporally challenging prospect. The use of inducible systems, epitope tags, and alternative techniques may provide opportunities for detecting elusive "hit and run" transcriptional silencing. Also see the video abstract herehttps://youtu.be/vgrsoP_HF3g . Abstract : Transcriptional repressors and activators may function by different mechanisms and may be resident or absent at different stages of gene regulation. Here, an example of how an activator and a "hit and run" repressor may function and how this would affect detection by assays such as chromatin immunoprecipitation (ChIP) is shown.